Circadian control of visual plasticity in arthropods. Issue 1 (2nd January 2016) - Mazzotta, G.M.; Costa, R.
Abstract : Animals living in a wide range of light intensities need mechanisms to regulate the sensitivity of their visual system to their ambient illumination level. A high degree of plasticity is, in fact, necessary to optimise the visual system's ability to respond to fluctuations in lighting conditions. A functional circadian clock regulating photoreception structures would confer a circadian footmark favouring environmental adaptation to visual information. A variety of rhythmic visual behaviours have been observed in numerous organisms: here we will describe the effects of circadian rhythms on visual performance in arthropods, provide examples of visually guided behaviours and describe how plasticity of the visual system is achieved in these animals.